Enhanced Recovery Programme (ERP) after Abdominal Surgery: Time to Change Practice - Hossain, AZM Mostaque; Haque, Nazma; Nafisa, Ali (Journal of Surgical Sciences, 2019)
Abstract not available Journal of Surgical Sciences (2014) Vol. 18 (1) : 28-34